Exploring the subjective well-being of elderly Orang Seletar indigenous people in Johor, Malaysia - Rosnon, Mohd Roslan; Abdul Razak, Muhammad Afiq; Jalaludin, Muhamad Luqmanudin; Dahamat Azam, Mohamad Naqiuddin (EnPress Publisher, 2024)
The subjective well-being (SWB) concept specific to the elderly Orang Asli is still vague, with limited research. Understanding SWB can give a holistic picture of elderly Orang Asli’s well-being status because SWB considers individual evaluations and perspectives based on life experiences in various dimensions relevant to the elderly Orang Asli’s culture, language, belief system, and lifestyle. Therefore, this paper aims to explore the concept of SWB of elderly Orang Seletar. An exploratory case study research design is implemented in this qualitative study. 15 informants who participated in an in-depth interview session in Kampung Bakar Batu Perling, Johor Bahru, and aged 50 years old and above. Based on the findings of the study, there were seven major themes in discussing the concept of SWB which are (i) sufficiency; (ii) comfort; (iii) satisfaction; (iv) preference/favorite; (v) happiness; (vi) tranquillity and (vii) awareness. The finding of the study shows that there were eight domains of SWB of elderly Orang Asli Seletar which are (i) physical health; (ii) mental health; (iii) family and community; (iv) sea and nature; (v) culture preservation; (vi) basic needs; (vii) education; and (viii) spiritual. In conclusion, SWB should be the core element to determine the development of elderly Orang Seletar to ensure their thrive. From mainstream society’s eye, elderly Orang Seletar’s lives may be seen as inadequate and modest. However, it is different from what is felt by them.